(3eYQGL GdfHj Udi Gddg Ydjg hSde QhGjI GHf YHGSs - (3GdbQTj GdgGTej, GHf YHGS, YHO Gddg Hf YHGS Hf YHO GdeWdH, J(B68(3g`s ((3edG eMeO CZGehG Hf Ydjs)
(3ChdgG (B:s
(3Qhi YHO Gddg GHf GdTGjH Yf CHj UGdM Yf YHO Gddg Hf YHGS QVj Gddg YfgeG HGdESfGO ajeG Qhj aj bUI GdeYQGL heG hQO Yf GdfHj Udi Gddg Ydjg hSde Efg bGd HjfeG CfG fGFe Hjf GdUaG hGdeQhI aj djdI PGJ QYO hHQbs
(3BNQgG (B:s
(3heG QCi aj GdLMje hGdRbhe hGdMjGJ hGdYbGQH dCYOGFg fSCd Gddg GdSdGeI hGdBNQI ef GdfGQ HLGg eMeO Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 95s
(3eYLe GdeDdajf(B: 2 / 249s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs